A Note on Operator Equations Describing the Integral - König, H.; Milman, V. (Журнал математической физики, анализа, геометрии, 2013)
We study operator equations generalizing the chain rule and the substitution rule for the integral and the derivative of the type f ○ g + c = I (Tf ○ g ∙ Tg), f, g є C¹(R), (1) where T : C¹ (R) → C(R) and where I is defined on C(R). We consider suitable conditions on I and T such that (1) is well-defined and, after reformulating (1) as V (f ○ g) = Tf ○ g ∙ Tg, f, g є C¹(R) (2) with V : C¹ (R) → C(R), give the general form of T, V and I. Simple initial conditions then guarantee that the derivative and the integral are the only solutions for T and I. We also consider an analogue of the Leibniz rule and study surjectivity properties there. Изучаем операторные уравнения, соответствующие цепному правилу и замене переменных f ○ g + c = I (Tf ○ g ∙ Tg), f, g є C¹(R), (1) где T : C¹(R) → C(R) и где I определен на C(R). Рассматриваем соответствующие условия на I и T такие, что (1) корректно определено и, после перенормировки (1) в форме V (f ○ g) = Tf ○ g ∙ Tg, f, g є C¹1(R) (2) с оператором V : C¹(R) → C(R), мы приводим общую форму T, V и I. Простые начальные условия гарантируют, что производная и интеграл являются единственными решениями для T и I. Также рассматриваем операторной аналог для правила Лейбница и изучаем его сюръективность.